Pathology of perinatal and early onset nephrotic syndrome - Guido Monga; Lorenzo Daniele; Gianna Mazzucco (Hygeia Press di Corridori Marinella, 2014)
Nephrotic syndrome rarely occurs in the first year of life. There are some cases which share the pathological changes observed in older children or in adults, but two forms, the congenital nephrotic syndrome of the Finnish type (CNF) and the diffuse mesangial sclerosis (DMS) show peculiar morphologic findings. CNF is characterized in its early phases by the focal dilation of the proximal tubules with formation of small cysts and by mesangial hypercellularity. With progression of the disease, tubular dilation spreads from the deep to the outer cortex and focal-segmental and global glomerulosclerosis become evident. DMS may be renal-limited or be associated with male pseudohermaphroditism and Wilm's tumor (Denys-Drash syndrome). It shows the increase of the mesangial matrix and mesangial hypercellularity in the early phases of the disease and extensive glomerulosclerosis in the later ones. Podocytes are hypertrophic around the sclerotic areas and form pseudocrescents. Tubular dilations and cysts may be present, but in lesser extent compared with CNF. Interstitial fibrosis occurs with increasing severity from the inner to the outer cortex. Apart from the negative reaction from nephrin in CNF, immunohistochemistry has no diagnostic relevance in both diseases. Electron microscopy shows in both diseases a diffuse effacement of the foot processes and microvillous transformation of the podocytes. Glomerular basement membrane may show changes recalling those found in Alport disease. Due to the rather similar changes in CNF and DMS, a pathological diagnosis may be difficult on small tissue specimens provided by needle biopsies. It follows that accurate clinical and genetic investigations are needed in addition to the pathological study.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken